Fatty acids and osteoarthritis: the MOST study. Issue 7 (July 2021) - Felson, D.T.; Misra, D.; LaValley, M.; Clancy, M.; Chen, X.; Lichtenstein, A.; Matthan, N.; Torner, J.; Lewis, C.E.; Nevitt, M.C.
Summary: Objective: Inflammation worsens joint destruction in osteoarthritis (OA) and aggravates pain. Saturated and n-6 fatty acids (FAs) increase, whereas n-3 FAs reduce inflammation. We examined whether FA levels affected the development of OA. Design: We studied participants from the Multicenter Osteoarthritis study (MOST) at risk of developing knee OA. After baseline, repeated knee x-rays and MRIs were obtained and knee symptoms queried through 60 month follow-up. Using baseline fasting samples, serum FAs were analyzed with standard assays. After excluding participants with baseline OA, we defined two sets of cases: those developing radiographic OA and those developing symptomatic OA (knee pain and radiographic OA). Controls did not develop these outcomes. Additionally, we examined worsening of MRI cartilage loss and synovitis and of knee pain using WOMAC and evaluated the number of hand joints affected by nodules. In regression models, we tested the association of each OA outcome with levels of saturated, n-3 and n-6 FAs adjusting for age, sex, BMI, education, race, baseline pain and depressive symptoms. Results: We studied 260 cases with incident symptomatic and 259 with incident radiographic OA. Mean age was 61 years (61% women). We found no signficant nor suggestive associations of FA levels with incident OA (e.g., for incident symptomatic OA, OR per s.d. increase in n-3 FA 1.00 (0.85, 1.18) nor with any OA outcome in knee or hand. Conclusion: Despite previously described effects on systemic inflammation, blood levels of FAs were not associated with risk of later knee OA or other OA outcomes.